EVALUATION OF THE ANTI-TYROSINASE-ANTI-AGING POTENTIAL AND METABOLITE PROFILING FROM THE BIOACTIVE FRACTION OF CORN COB (ZEA MAYS L.) - HARAHAP, ARMITA; TRIAMARTA, SUCI; KHARISMA, DINDA; HANIFAH, WIWIK; IQBAL, MUHAMMAD; ARIFA, NURWAHIDATUL; ISMED, FRIARDI (International Journal of Applied Pharmaceutics, 2024)
Objective: Maize (Zea mays L.) is a crop that has been widely cultivated in Indonesia. Using corn kernels on a large scale will produce much corn cob waste, usually unused. According to the literature search, corn cobs’ phytochemical studies and pharmacological activities still need to be improved. This study aims to determine the content of secondary metabolites (metabolite profiling) and their antityrosinase and anti-aging potential. Methods: Corn cobs were macerated with methanol and fractionated with n-hexane, ethyl acetate, and butanol. The phytochemical profiling approach of the methanol extract was performed by liquid chromatography-mass spectra (LC-MS/MS). Anti-tyrosinase and anti-aging bioactivity were evaluated by thin layer chromatography (TLC)-bioautography and IC50 spectrophotometrically. Results: The evaluation results show that the butanol fraction leads to a potential value (IC50 99.92 µg/ml). Several compounds, especially flavonoid compounds (including catechin; kaempferol 3-arabinofuranoside 7-rhamnoside; 6,8-Di-C-beta-D-arabino pyranosyl apigenin; 5,7-Dihydroxy-8,4’-dimethoxyisoflavone) were identified by LC-MS/MS by comparing the molecular mass of MS/MS data with literature data. Conclusion: Based on this study, it can be concluded that butanol is the fraction that most actively inhibits tyrosinase, elastase, and collagenase enzymes, which means it potentially becomes a new anti-aging candidate.